An??lise da a????o do laser de baixa pot??ncia na cicatriza????o de feridas em ratos idosos - Fi??rio, Franciane Barbieri (2014)
The optimization of time for the healing of a wound is very important, in view of the consequences it may cause, and this optimization becomes even more relevant in individuals with advanced age, where the repair is slower. The objective of this study was to evaluate the effect of low power laser on healing in an experimental model of skin wounds in aged rats. The skin wound was produced on the back using a "punch" 8mm diameter. 45 rats were males, of which 15 young people (?? 30 days) and 30 elderly (?? 500 days), divided into three groups, control young, control age and treated which underwent skin wound, and the group old treated received low-level laser treatment (30 mW, power density of 1.07 W / cm2), the area 0,028cm2 beam and wavelength ??660nm, active means of InGaAlP. Analyses were conducted to check the effects of laser on the expression of collagen type I and III, MMP-3, MMP-9, TIMP-2 and VEGF by immunohistochemical staining, IL-6 expression by RT-PCR and CINC-1 expression by ELISA. The results show that the laser decreased IL-6 and IL-8, MMP-3 and MMP-9, increased levels of TIMP-2 and VEGF, and favored collagen I and III deposition at the three time points (3, 7 and 14 days). We can conclude that laser therapy with the parameters used was effective in the treatment of skin wounds in aged animals at different stages of the process of tissue repair by modulating the expression of mediators of tissue repair and collagen deposition.